Developing the Person-Centered Emergency Care Assessment: A Holistic Performance Framework for Indonesian Hospital - Saputera, Bayu; Pribadiyono, Pribadiyono; Suwitho, Suwitho (Transpublika Publisher, 2024)
The emergency department at one of the Indonesian Public Hospital faces challenges of overcrowding, inadequate performance assessments, and the lack of a holistic team evaluation system, adversely affecting service quality and patient outcomes. This study proposes the Person-Centered Emergency Care Assessment (PECAS), a performance assessment system aligned with the person-centered care paradigm. Employing a qualitative approach and hermeneutic method, data were collected through interviews, observations, and document studies involving directors, medical and nursing committees, team members, and patients. The PECAS instrument was developed in three stages: exploring indicators, constructing the instrument, and determining methodologies, with a 360-degree evaluation approach to capture diverse perspectives. The trial results indicated team performance ranged from